CropSense – A Smart Agricultural System using IoT - Athira Nair,; Anna Saji,; Aneesa James,; Deepa Joseph, (Journal of Electronic Design Engineering, 2019)
Agriculture plays a vital role in the development of a growing economy. As far as India is concerned, agriculture accounts for 18% of the Gross Domestic Product (GDP). Problems encountered in this sector have reduced crop productivity and the quality of crop production. The solution lies in modernizing conventional farming techniques by engaging new age technology to tackle problems that are caused due to manual and external intervention. Traditional methods involve constant monitoring from time to time that is exhausting for the farmers as well as results in reduced crop quality. These methods also consume a lot of water and cause either over-irrigation or under-irrigation. Wild animals, pests and rodents are also major threats to crops. Installing cameras requires constant network connectivity and may not be efficient enough to detect motion and sound caused by the intruder. This project proposes smarter ways of controlling irrigation and crop security of an agricultural field using the Internet of Things (IoT). In order to control the system, the collected field data is analyzed using Raspberry Pi an onboard computer and alert is given. The intruder image is captured using Pi Camera and sent to the farmer’s phone. The system is turned ON/OFF as and when required using an app installed in the farmer's smart phone. This ensures timely irrigation only when the field is dry as well as warns the farmer of a possible wild animal attack. Thus, CropSense provides a feasible solution to farmers and helps in enhancing crop quality and productivity in the long run.